2020
DOI: 10.1371/journal.pone.0231334
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold stochastic vestibular stimulation affects balance-challenged standing and walking

Abstract: Subthreshold stochastic vestibular stimulation (SVS) is thought to enhance vestibular sensitivity and improve balance. However, it is unclear how SVS affects standing and walking when balance is challenged, particularly when the eyes are open. It is also unclear how different methods to determine stimulation intensity influence the effects. We aimed to determine (1) whether SVS affects stability when balance is challenged during eyes-open standing and overground walking tasks, and (2) how the effects differ ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Iwasaki et al ( 2018 ) found that nGVS increased gait speed and stride length, and decreased stride time, in people with BVP during overground walking. A similar effect was found in healthy young people during overground walking and walking on unsteady surfaces (Piccolo et al, 2020 ). To the contrary, Wuehr et al ( 2016a , b ) found there was no change in spatiotemporal gait parameters in healthy or BVP populations during walking at slow, preferred, and fast speeds.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Iwasaki et al ( 2018 ) found that nGVS increased gait speed and stride length, and decreased stride time, in people with BVP during overground walking. A similar effect was found in healthy young people during overground walking and walking on unsteady surfaces (Piccolo et al, 2020 ). To the contrary, Wuehr et al ( 2016a , b ) found there was no change in spatiotemporal gait parameters in healthy or BVP populations during walking at slow, preferred, and fast speeds.…”
Section: Discussionsupporting
confidence: 73%
“…This finding is noteworthy, as lateral gait variance has been cited as a defining feature of gait imbalance in people with BVP (Schniepp et al, 2019 ). Decreased step width variability (Wuehr et al, 2016b ; Piccolo et al, 2020 ) and improved stability during lateral perturbation of the support surface (Mulavara et al, 2015 ) have also been found in nGVS studies on young healthy people, strengthening support for the role of nGVS to augment vestibular afferents and maintain stable gait (Schniepp et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…This is an important first step toward more widespread use of this technology when applying nGVS. Sixth, our noisy stimulation parameters matched several studies [ 9 , 10 , 38 ] but differed from many others [ 4 , 5 , 7 , 8 , 17 ]. How different noisy stimulation parameters influence HbO and HbR concentrations is unclear at this time.…”
Section: Discussionmentioning
confidence: 65%
“…If they could not, we increased the current by another step. Once participants reported feeling the stimulation, we set the signal to 80% of this current value [ 5 , 8 , 17 ]. Subsequently, we confirmed that participants did not feel the current (average peak current: 183 +/− 95 µA), which we delivered as the stimulation magnitude for the experimental session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation